2020
DOI: 10.1093/jue/juaa029
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the response of odonates (dragonflies and damselflies) to a tropical urbanization gradient

Abstract: Understanding species responses to urbanization is important to realize their specific conservation needs. Odonates (dragonflies and damselflies) are freshwater insects perceived as good ecological indicators. To investigate responses of tropical odonates to an urbanization gradient, we sampled adult odonates along an urbanization gradient at six sites along the Mula River across Pune City, Maharashtra, India. For species–habitat analysis, we first performed a variable reduction using principal component analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Three abundant species were found which can be called as generalists across the study region, namely, I. rapax, C. servilia, and D. trivialis. Jere et al (2020) reported C. servilia as a generalist and I. rapax as an urban specialist. Our results regarding generalists are partially in line with Jere et al (2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three abundant species were found which can be called as generalists across the study region, namely, I. rapax, C. servilia, and D. trivialis. Jere et al (2020) reported C. servilia as a generalist and I. rapax as an urban specialist. Our results regarding generalists are partially in line with Jere et al (2020).…”
Section: Resultsmentioning
confidence: 99%
“…Jere et al (2020) reported C. servilia as a generalist and I. rapax as an urban specialist. Our results regarding generalists are partially in line with Jere et al (2020). During the survey, a Lestes species similar to L. malabaricus was recorded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In those habitats, I. senegalensis plays a vital role in rice pest control (Chakraborty et al, 2016; Pavithran, Chitra, and Ramanathan, 2020) and mosquito control (Choo et al, 2021). However, anthropogenic disturbance, like pesticide application in rice fields, negatively affects diversity of arthropods including odonates (Jere et al, 2020; Sugita et al, 2018) and thus might shape the genetic structure of populations (Sato et al, 2008; Vickruck & Richards, 2017). Growing evidence shows that anthropogenic landscapes could strongly reduce population exchange via habitat fragmentation (Cayuela et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…individuals are the most vulnerable ones in the face of environmental disturbances Possibly, building up a large body requires long developmental periods, more food and, consequently, more risks(Suhonen et al, 2022).Different types of stressors in uence different species inside an order (e.g Luke et al, 2017;Seidu et al, 2018;Huikkonen et al, 2019;Jere et al, 2020)…”
mentioning
confidence: 99%